Seasonal dynamics of thraustochytrids in mangrove rhizospheres for microbial interactions, PUFA production - Kalidasan Kaliyamoorthy; Kathiresan Kandasamy; Suchana Chavanich; Niyom Kamlangdee; Nambali Valsalan Vinithkumar; Voranop Viyakarn (Scientific Reports)
Abstract This study investigated seasonal variations of thraustochytrids in rhizosphere soil collected from two mangrove species Rhizophora apiculata and Avicennia marina in natural and planted mangrove stands. Thraustochytrid counts were higher in the natural mangrove stand than in the planted site. The counts varied seasonally, being highest in the post-monsoon season followed by summer, monsoon, and pre-monsoon. Thraustochytrid counts exhibited positive correlations (p < 0.01) with counts of Total heterotrophic bacteria (THB), azotobacters, actinobacteria, fungi, yeasts, and Trichoderma. However, a negative correlation was observed with cyanobacteria. The counts also had positive correlation with silt, clay, nitrogen, phosphorus, potassium, chromium, copper, magnesium, cadmium, zinc and redox potential, but, negative correlations with temperature, pH, pore water salinity, total organic carbon and sand content of the soil samples. In the present study, 113 thraustochytrid strains were isolated from mangrove habitats. However, only 48 pure cultures survived after being sub-cultured three times. Based on survivability, color, and shape, two isolates from each sampling site in each season were selected. The predominant 24 isolates were identified based on their morphological, and molecular characteristics and were classified under five genera: Thraustochytrium, Schizochytrium, Botryochytrium, Parietichytrium, and Aurantiochytrium. Among the isolates, Aurantiochytrium sp. (AKTSK-06) produced the highest biomass of 15.71 g/L in the post-monsoon season (January-March, 2023), and Aurantiochytrium sp. (PVTSK-03) accumulated the highest lipid content of 61.33%. Thraustochytrids were found to contain Omega-3 poly unsaturated fatty acids (PUFAs), such as EPA up to 8.89% in Aurantiochytrium sp. (VRTSK-01), DPA up to 9.65% in Aurantiochytrium sp. (AKTSK-03), and DHA up to 47.46% in Aurantiochytrium sp. (AKTSK-06). Thus, mangroves provide an ideal ecological niche for thraustochytrids with an abundant supply of omega-3 fatty acids for potential industrial applications.